Interpersonal Communication of Mc Donald's Employees In Improving Customer Satisfaction a t Mc Donald's Karang Satria - Iksan, Akmal Nur; Sanjaya, Feri (Yayasan Sinergi Kawula Muda, 2023)
Along with the development of fast food business time is also growing and increasing which makes the fast food business competition in Indonesia is becoming increasingly stringent. With this intense competition makes a fast food business continues to offer its products with a variety of innovations, especially in communicating with customers.improve communication skills, provide the best service as well, and meet all the needs required by its customers. It becomes interesting to examine, whether customer satisfaction can be improved by an interpersonal communication conducted by a fast food employee to its customers. This study aims to determine the Interpersonal communication of Mc Donald's employees in improving customer satisfaction at Mc Donald's Karang Satria. This study uses interpersonal communication theory from Devito with dimensions of openness, empathy, support, positivity, similarity and also uses customer satisfaction theory from Indrasari with dimensions of Product Quality, Service Quality, emotional, price and cost. This study uses qualitative research methods with interview data collection techniques, observation, and documentation. The results of this study show that interpersonal communication of mc Donald's employees in improving customer satisfaction has been running well in all dimensions, but there are three dimensions that are still not done well, namely related to positivity, service quality and product quality. The conclusion of the study showed that interpersonal communication plays an important role in improving customer satisfaction.